Malaysian students' negotiation of identity through spoken academic discourse - Zurina Khairuddin
Identity is theorised as always changing, constructed, negotiated, partial, and conflicting (Norton, 2000) and is also influenced by the environment or culture individuals belong to (Ang, 2011). Identity is also not pre-existing to interaction but it is situated and co-constructed within an exchange. Ridwan (2017) observes how students assume multiple identities that could be conflicting during the identity negotiation process. This process occurs in academic settings with the members of the academic communities, both tutors and peer, when discussing academic topics. The study adopts the theory of Communities of Practice (CoP) (Wenger, 1998) to define the multilingual seminars in the UK and Malaysia and Sacks, Schegloff and jefferson's (1974) Conversation Analysis approach to analyse talk-in-interaction and identify the communicative styles of the Malaysian students. This research highlights different interactional styles among Malaysian students in seminars in the UK (MSUK) and Malaysian students at a comparable international university in their home country (MSM); it explores their perceptions of their own interactions and interactions by other students; it investigates their identity construction in the two contexts; and the strategies they resort to in a group to negotiate their (dis)engagement. Nine MSUK and 11 MSM were chosen as participants. The data for this study was collected by observing these students interact in seminars, and then through interviewing and focus group discussions. The language data were analysed employing Bucholtz and Hall's (2005) identity-in-interaction framework. Adopting the principles of emergence and indexicality (Bucholtz & Hall, 2005), the findings of this study suggest that MSUK and MSM constructed and negotiated flexible identities particularly agentive and accommodative when they were in seminars. MSUK also constructed and negotiated resistant identity while MSM did not. These identities were interpreted based on the students' interactional behaviour and their own perceptions of their interactions. The study concludes that academic identity is flexible and students construct and negotiate their self based on the contexts they are in.